Optimization of oxidative coupling of methane using response surface methodology - Saidina Amin, Nor Aishah; Zakaria, Zaki Yamani (Penerbit UTM Press, 2003)
Oxidative Coupling of Methane (OCM) reaction over Li/MgO catalyst was optimized using experimental design from ‘Statsoft Statistica’ version 6.0 software. The manipulated variables chosen in this study were operating temperature, total flow rate per weight of catalyst (F/W), and weight percent of Li doped into MgO catalyst, whilst methane conversion, C2 product selectivity, and C2 product yield were the responses. The equation model was tested with Anova analysis with 99% degree confidence. The Response Surface Methodology (RSM) was employed to determine the optimum responses. By means of variance analysis and additional experiments, the adequacy of this model was confirmed.